Does Environmental, Social, and Governance (ESG) Disclosure Lead to Greater Firm Value? Unveiling the Mediating Role of Financial Performance - Hendi Rohendi; Yeti Apriliawati (Finance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2026)
Previous empirical findings on the relationship between ESG disclosure and firm value have shown inconsistent results. Some studies suggest that ESG disclosure enhances firm value, while others view it as a cost burden or a managerial tool used for personal gain. These inconsistencies create uncertainty for stakeholders in making economic decisions and indicate that previous theoretical models may be incomplete. Addressing this gap, the current study introduces a new approach by incorporating financial performance as a mediating variable in the relationship between ESG disclosure and firm value. This study utilized panel data from 51 companies listed on the Indonesia Stock Exchange, covering the period from 2015 to 2022, with a total of 357 firm-year observations. Hypothesis testing was conducted using the PLS–SEM methodology through the WarpPLS 8.0 software. The results indicate that ESG disclosure does not have a significant direct effect on firm value. This study has three contributions. First, it provides an answer to previous studies showing inconsistent directions. Second, the outcomes lend support to the proposition that financial performance bridges the influence of ESG disclosure on firm value. Third, it provides an understanding to company managers that ESG disclosure is important to improving financial performance. The implications of this research indicate that ESG disclosure can be incorporated as a strategy to improve financial performance and indirectly strengthen firm value.